Studying the delignification of wood fibers using laccase enzymes - Nor Zawani, Zainuddin (2013)
The process to subtract lignin from the lignocelluloses compound requires a lot of chemical amount, energy contribution and also a huge sum of financial and ecological cost. Furthermore, a large amount of expensive chemical required is not reliable in the long term because of its limited resources. Therefore, the lignin conversion process should be substitute with a better and economical way to convert lignin into marketable product. Fortunately, there is great interest in developing industrial application of enzymes of microorganisms to degrade lignin. Therefore, the study of delignification using laccase enzyme were conducted using different temperature and the pH. In this study, the removal of lignin is from the wood fiber using batch enzymatic hydrolysis. Thus, in the enzymatic hydrolysis, the temperature and the pH value of the buffer solution is being studied by manipulate it into